Ketidakadilan Distribusi Manfaat dalam Pengelolaan Sumber Daya Alam di Kalimantan Timur: Telaah Kritis atas Implementasi Pasal 33 UUD 1945 - Arundaya, Maheswari; Syifa, Triyara Annisa Nur; Arifin, Sheila Aurelia; Suryaningsih, Suryaningsih (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The unfair distribution of benefits in natural resource management is a persistent legal and institutional problem in Indonesia, particularly in East Kalimantan, even though Article 33 of the 1945 Constitution of the Republic of Indonesia explicitly places state control over natural resources as a constitutional instrument for realizing the welfare of the people. This study focuses on the gap between the constitutional norms of Article 33 of the 1945 Constitution and the practice of natural resource management, which is still rife with abuse of authority and unequal distribution of benefits. This study aims to critically analyze the implementation of Article 33 of the 1945 Constitution in the policies and practices of natural resource management in East Kalimantan and to identify the institutional factors that influence distributive injustice. The main problems of this research lie in the weak design of natural resource management institutions, the fragmentation of authority among state actors, and the strong intervention of political and economic interests that open up opportunities for corruption. This study uses a qualitative research method with a normative juridical approach combined with institutional analysis. Data was obtained through a literature study of laws and regulations, relevant court decisions, official reports from the Corruption Eradication Commission related to the evaluation of the National Movement for the Preservation of Natural Resources (GNP SDA), and academic literature, which was analyzed using the Institutional Analysis and Development (IAD) framework. The results of the study show that the inconsistency between constitutional rules and policy implementation is reflected in weak oversight mechanisms, overlapping sectoral regulations, and low community participation in decision-making on natural resource management. These conditions lead to the concentration of economic benefits in certain groups, while local communities bear the social, economic, and ecological burdens. The novelty of this study lies in the use of the IAD framework to explain the unfair distribution of natural resource benefits from a constitutional law perspective. This study implies the need for institutional reform, strengthening legal accountability, and restructuring natural resource management policies to be in line with the principles of distributive justice and the constitutional mandate of Article 33 of the 1945 Constitution.